Risk Factors of Musculoskeletal Disorders (MSDs) among Kota Kinabalu, Sabah Firefighters: A Preliminary Study - Tiong, Alastair; Maakip, Ismail (RSF Conference Series: Business, Management and Social Sciences, 2023)
This study examined the relationship between predictors such as demographical aspect, task characteristics, physical demands, work-life balance, workstyle, psychosocial factors, and MSD among firefighters that was conducted at four fire stations under Kota Kinabalu Zone in Sabah (n=130 firefighters participated). The questionnaires used in the present study consist of a demographical aspect, task characteristics scale, physical demands scale, work-life balance scale, workstyle scale, Work Organization Assessment Questionnaire, Mental Health Scale, and musculoskeletal disorders (MSDs). The data was analysed with the use of SPSS version 22.0. The results show that task characteristics, physical demands, work-life balance, workstyle, and Mental Health Scale were significantly related to MSDs among Kota Kinabalu, Sabah firefighters. Firefighters did experience MSD due to overweighted equipment, lack of rest, accidents, and traumatic events like death among victims or teammates, which lead to depression and stress.